Método de monitoramento da eficiência da insensibilização elétrica por eletronarcose: situação atual e perspectivas de melhorias - Dvojatzki, Pricila (2014)
The concept of animal welfare was previously established within a very wide range of parameters and few scientific aspects, therefore not easily accepted by producers countries. Scandinavian countries, followed by France, were the first to adopt more pragmatic concepts of wellness and outlined standards for breeding. With the increase of requirements for animal welfare, the aim was drawn to all poultry slaughterhouses and focused to the electric stunning, which is the most accepted method and used worldwide for immobilization of the birds before slaughter. Most developed countries have laws for the humane slaughter of farm animals, which include species of birds. These laws are designed to ensure that the animals are killed quickly and without pain and suffering, because the incidence of damage to poultry occurs 24 hours before slaughter, during the capture and transport steps, however, the electric stun is also considered an area of stress. In order to provide animal welfare at slaughter, it has been worked with the analysis of behavioural parameters to assess the efficiency of electrical stunning by electronarcosis. Afterwards, it has been proposed improvements to adopt the production process.